Wettability and sp2/sp3 ratio effects on supercapacitor performance of N-doped hydrogenated amorphous carbon nanofoam - Subrata Ghosh; Giacomo Pagani; Andrea Macrelli; Alberto Calloni; Gianlorenzo Bussetti; Andrea Lucotti; Matteo Tommasini; Raffaella Suriano; Marco Agozzino; Giorgio Divitini; Yurii P. Ivanov; Veronica Piazza; et al. (Chemical Engineering Journal, 2025)

Loss-of-heat-sink transient simulation with RELAP5/Mod3.3 code for the ATHENA facility - T. Del Moro; F. Giannetti; P. Cioli Puviani; I. Di Piazza; D. Diamanti; M. Tarantino (Annals of Nuclear Energy, 2025)

Evaluation of real-time fluorescence sensors and benchtop fluorescence for tracking and predicting sewage contamination in the Tijuana River Estuary at the US-Mexico border - Natalie Mladenov; Trent Biggs; Keyshawn Ford; Stephany Garcia; Yongping Yuan; Alexandra Grant; Elise Piazza; Elisa Rivera; Federick Pinongcos; Scott P. Keely; Callie Summerlin; Jeffrey A. Crooks; et al. (Science of The Total Environment, 2024)

The efficacy of cognitive stimulation, cognitive training, and cognitive rehabilitation for people living with dementia: a systematic review and meta-analysis - Alice Paggetti; Ylenia Druda; Francesco Sciancalepore; Francesco Della Gatta; Antonio Ancidoni; Nicoletta Locuratolo; Paola Piscopo; Luca Vignatelli; Luciano Sagliocca; Antonio Guaita; Piero Secreto; Andrea Stracciari; et al. (GeroScience, 2024)
Cognition-oriented treatments (COTs) are a group of non-pharmacological treatments aimed at maintaining or improving cognitive functioning. Specific recommendations on the use of these interventions in people living with dementia (PLwD) are included in the Italian Guideline on the Diagnosis and Treatment of Dementia and Mild Cognitive Impairment, developed by the Italian National Institute of Health. This systematic review and meta-analysis, based on the GRADE methodology, is part of the guideline. Considered outcomes included the cognitive functions, quality of life, and functional abilities of PLwD, taking into account disease severity, modality and system of delivery, and form of the intervention. The effectiveness of these interventions on caregivers’ outcomes was also assessed. Both group and individual cognitive stimulation were reported as effective in supporting cognitive functions in PLwD at any degree of severity. Individual cognitive training and group cognitive training were reported as effective in improving global cognitive functions in people with mild dementia. Cognitive rehabilitation appeared to be effective only in improving the functional abilities of people with mild dementia. Cognitive rehabilitation appeared to be the most effective in improving caregivers’ outcomes, with results suggesting a reduction in care burden. The observed differences in the effectiveness of these interventions in people with different disease severity can be explained by the intrinsic characteristics of each intervention. Despite the large number of available studies, a high clinical, statistical, and methodological heterogeneity was observed. More methodologically rigorous studies are needed to clarify the effectiveness of each protocol and modality of intervention.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

S13-02 Update on EFSA's activities in the area of cumulative risk assessment of pesticides - S. Levorato; V. Costanzo; G. Di Piazza; B. Dujardin; G. Giner; P. Medina; L. Mohimont; E. Solazzo (Toxicology Letters, 2024)

Biochemical and molecular biomarkers and their association with anthropogenic chemicals in wintering Manx shearwaters (Puffinus puffinus) - Patricia P. Serafini; Bárbara P.H. Righetti; Ralph E.T. Vanstreels; Leandro Bugoni; Clei E. Piazza; Daína Lima; Jacó J. Mattos; Cristiane K.M. Kolesnikovas; Alice Pereira; Marcelo Maraschin; Isadora Piccinin; Tim Guilford; et al. (Marine Pollution Bulletin, 2024)

Carotid artery stenting during endovascular thrombectomy for acute ischemic stroke with tandem occlusion: the Italian Registry of Endovascular Treatment in Acute Stroke - Fabrizio Sallustio; Giovanni Pracucci; Manuel Cappellari; Valentina Saia; Alfredo Paolo Mascolo; Federico Marrama; Roberto Gandini; Giacomo Koch; Marina Diomedi; Federica D’Agostino; Alessandro Rocco; Valerio Da Ros; et al. (Acta Neurologica Belgica, 2023)

Role of the YehD fimbriae in the virulence‐associated properties of enteroaggregative Escherichia coli - Jorge Soria‐Bustos; Waleska Saitz; Abraham Medrano; Cristina Lara‐Ochoa; Zineb Bennis; Valerio Monteiro‐Neto; Camilla Itapary dos Santos; Josias Rodrigues; Rodrigo T. Hernandes; Jorge A. Yáñez; Javier Torres; Fernando Navarro‐García; et al. (Environmental Microbiology, 2022)
Summary The interaction of enteroaggregative Escherichia coli (EAEC) strains with the colonic gut mucosa is characterized by the ability of the bacteria to form robust biofilms, to bind mucin, and induce a local inflammatory response. These events are mediated by a repertoire of five different aggregative adherence fimbriae variants (AAF/I‐V) typically encoded on virulence plasmids. In this study, we report the production in EAEC strains of a new Y eh D f imbriae (YDF), which is encoded by the chromosomal gene cluster yehABCD , also present in most E. coli strains. Immuno‐labelling of EAEC strain 042 with anti‐AAF/II and anti‐YDF antibodies demonstrated the presence of both AAF/II and YDF on the bacterial surface. We investigated the role of YDF in cell adherence, biofilm formation, colonization of spinach leaves, and induction of pro‐inflammatory cytokines release. To this aim, we constructed yehD deletion mutants in different EAEC backgrounds (strains 17‐2, 042, 55989, C1010, 278‐1, J7) each harbouring one of the five AAFs. The effect of the YDF mutation was strain dependent and AAF independent as the lack of YDF had a different impact on the phenotypes manifested by the different EAECs tested. Expression of the yehABCD operon in a E. coli K12 ORN172 showed that YDF is important for biofilm formation but not for adherence to HeLa cells. Lastly, screening of pro‐inflammatory cytokines in supernatants of Caco‐2 cells infected with EAEC strains 042 and J7 and their isogenic Δ yehD mutants showed that these mutants were significantly defective in release of IL‐8 and TNF‐α. This study contributes to the understanding of the complex and diverse mechanisms of adherence of EAEC strains and identifies a new potential target for preventive measures of gastrointestinal illness caused by EAEC and other E. coli pathogroups.

A first-of-its-kind multi-model convection permitting ensemble for investigating convective phenomena over Europe and the Mediterranean - Erika Coppola; Stefan Sobolowski; E. Pichelli; F. Raffaele; B. Ahrens; I. Anders; N. Ban; S. Bastin; M. Belda; D. Belusic; A. Caldas-Alvarez; R. M. Cardoso; et al. (Climate Dynamics, 2020)

Discontinuation of non-anti-TNF drugs for rheumatoid arthritis in interventional versus observational studies: a systematic review and meta-analysis - Fernanda S. Tonin; Laiza M. Steimbach; Leticia P. Leonart; Vinicius L. Ferreira; Helena H. Borba; Thais Piazza; Ariane G. Araújo; Fernando Fernandez-Llimos; Roberto Pontarolo; Astrid Wiens (European Journal of Clinical Pharmacology, 2018)

Phenolic compounds (hydroxycinnamic acids, flavan-3-ols, flavonols) profile in fruit of Italian peach varieties - D. Ceccarelli; A. M. Simeone; P. Nota; M. G. Piazza; C. Fideghelli; E. Caboni (Plant Biosystems, 2016)

Differential gene transcription, biochemical responses, and cytotoxicity assessment in Pacific oyster Crassostrea gigas exposed to ibuprofen - Miguel A. S. Serrano; Maria Gonzalez-Rey; Jacó J. Mattos; Fabrício Flores-Nunes; Álvaro C. P. Mello; Flávia L. Zacchi; Clei E. Piazza; Marília N. Siebert; Rômi S. Piazza; Diana Alvarez-Muñoz; Sara Rodriguez-Mozaz; Damià Barceló; et al. (Environmental Science and Pollution Research, 2015)

Macrofungi as ecosystem resources: Conservation versus exploitation - M. Zotti; A. M. Persiani; E. Ambrosio; A. Vizzini; G. Venturella; D. Donnini; P. Angelini; S. Di Piazza; M. Pavarino; D. Lunghini; R. Venanzoni; E. Polemis; et al. (Plant Biosystems, 2013)

Fungal biodiversity and in situ conservation in Italy - G. Venturella; E. Altobelli; A. Bernicchia; S. Di Piazza; D. Donnini; M. L. Gargano; S. P. Gorjòn; V. M. Granito; A. Lantieri; D. Lunghini; A. Montemartini; F. Padovan; et al. (Plant Biosystems, 2011)

Erratum to: Short- and Long-Term Response of Deteriorating Brackish Marshes and Open-Water Ponds to Sediment Enhancement by Thin-Layer Dredge Disposal - Megan K. La Peyre; Bryan Gossman; Bryan P. Piazza (Estuaries and Coasts, 2011)

Short- and Long-Term Response of Deteriorating Brackish Marshes and Open-Water Ponds to Sediment Enhancement by Thin-Layer Dredge Disposal - Megan K. La Peyre; Bryan Gossman; Bryan P. Piazza (Estuaries and Coasts, 2009)

Anticooperativity in diffusion-controlled reactions with pairs of anisotropic domains: a model for the antigen–antibody encounter - F. Piazza; P. De Los Rios; D. Fanelli; L. Bongini; U. Skoglund (European Biophysics Journal, 2005)

Relationships between individual sensitivity to CS- and cocaine-induced reinstatement in the rat - V. Deroche-Gamonet; A. Martinez; M. Le Moal; P. V. Piazza (Psychopharmacology, 2003)

Study of the addictive potential of modafinil in naive and cocaine-experienced rats - Deroche-Gamonet V.; Darnaudéry M.; Bruins-Slot L.; Piat F.; M. Le Moal; Piazza P. (Psychopharmacology, 2002)

A maize r1 gene is regulated post-transcriptionally by differential splicing of its leader - A. Procissi; P. Piazza; C. Tonelli (Plant Molecular Biology, 2002)

SR141716, a CB1 receptor antagonist, decreases the sensitivity to the reinforcing effects of electrical brain stimulation in rats - V. Deroche-Gamonet; M. Le Moal; P. Piazza; P. Soubrié (Psychopharmacology, 2001)

Sensitization to the motor effects of contingent infusions of heroin but not of κ agonist RU 51599 - Michela Marinelli; Michel Le Moal; P. V. Piazza (Psychopharmacology, 1998)